Recent Developments in the Chemistry of Heteroaromatic N-Oxides - Wang, Youliang; Zhang, Liming (Synthesis, 2015)
Selected developments in the chemistry of heteroaromatic N-oxides since 2001 are presented in this review. The use of these N-oxides, both in late-transition-metal-catalyzed oxidations of carbon–carbon triple bonds and in regioselective C–H functionalizations of the heteroarene, are contemporary topics of interest and the focus of the discussion.1 Introduction2 Synthesis of Heteroaromatic N-Oxides2.1 Direct Oxidation of Hindered Heteroarenes2.2 Through Construction of Heteroaromatic Rings3 Heteroaromatic N-Oxides as Oxidants3.1 Alkyne Oxidation3.2 Allene Oxidation3.3 Carbene Oxidation4 Heteroaromatic N-Oxides as Substrates4.1 Deoxygenative ortho-C–H Functionalization with Prior Activation4.2 Deoxygenative ortho-C–H Functionalization with Nonstabilized Carbanions4.3 Nondeoxygenative C–H Functionalization4.3.1 ortho-C–H Functionalization4.3.2 N-Oxide Directed ortho-Alkyl C–H Functionalization4.3.3 N-Oxide Directed Remote C–H Functionalization4.4 1,3-Dipolar Cycloaddition5 Conclusion and Outlook
Keywords: oxidations; alkynes; cycloadditions; carbenes; pyridines